Cardiac Remodeling in Heart Failure: Role of Pyroptosis and Its Therapeutic Implications - Chai, Ruoning; Xue, Wenjing; Shi, Shuqing; Zhou, Yu; Du, Yihang; Li, Yuan; Song, Qingqiao; Wu, Huaqin; Hu, Yuanhui (Frontiers in Cardiovascular Medicine, 2022)
Pyroptosis is a kind of programmed cell death closely related to inflammation. The pathways that mediate pyroptosis can be divided into the Caspase-1-dependent canonical pathway and the Caspase4/5/11-dependent non-canonical pathway. The most significant difference from other cell death is that pyroptosis rapidly causes rupture of the plasma membrane, cell expansion, dissolution and rupture of the cell membrane, the release of cell contents and a large number of inflammatory factors, and send pro-inflammatory signals to adjacent cells, recruit inflammatory cells and induce inflammatory responses. Cardiac remodeling is the basic mechanism of heart failure(HF) and the core of pathophysiological research on the underlying mechanism. A large number of studies have shown that pyroptosis can cause cardiac fibrosis, cardiac hypertrophy, cardiomyocytes death, myocardial dysfunction, excessive inflammation, and cardiac remodeling. Therefore, targeting pyroptosis has a good prospect in improving cardiac remodeling in HF. In this review, the basic molecular mechanism of pyroptosis is summarized, the relationship between pyroptosis and cardiac remodeling in HF is analyzed in-depth, and the potential therapy of targeting pyroptosis to improve adverse cardiac remodeling in HF is discussed, providing some ideas for improving the study of adverse cardiac remodeling in HF.